2016
DOI: 10.1201/b17096
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Modeling Using R

Abstract: When searching for a planar line, if given no further information, one should adopt a logarithmic spiral strategy (although unproven).This brief paper is concerned entirely with geometry in the plane and continues a thought in [1]. If a line intersects a circle in one or two points, we say that the line strikes the circle. If a line intersects a circle in exactly one point (that is, if the line is tangent to the circle), we say that the line touches the circle.Let f be a nonnegative, continuously differentiabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
137
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(140 citation statements)
references
References 5 publications
0
137
0
3
Order By: Relevance
“…These three parameters were calculated and presented in Table 4. While comparing models obtained from maximum likelihood approach, the lower LL Full can be used as a sign of outperformance, given that fitted models have the same sam- ple and dependent variable (Finch et al, 2014). As can be seen in Table 4, the PPO model provides the lowest LL Full ; therefore, it outperforms the other two models.…”
Section: Resultsmentioning
confidence: 97%
“…These three parameters were calculated and presented in Table 4. While comparing models obtained from maximum likelihood approach, the lower LL Full can be used as a sign of outperformance, given that fitted models have the same sam- ple and dependent variable (Finch et al, 2014). As can be seen in Table 4, the PPO model provides the lowest LL Full ; therefore, it outperforms the other two models.…”
Section: Resultsmentioning
confidence: 97%
“…6 indicates that residuals appear to be normally distributed despite the fact that there might be some issues on the low end of the distribution of residuals. However, Finch et al (2014) argue that the ceiling effect might play a role in such models, especially when a nontrivial number of respondents select the minimum scores for global warming concern.…”
Section: Multi-level Modelingmentioning
confidence: 97%
“…Examination of the reduction in tau [(8.35-7.34)/8.35); Singer, 1998;] for the between person variance, and the change in R 2 for within person variance ((1À(7.34 + 5.99/8.35 + 6.87)) for the internalizing problems and intrapersonal strengths models indicated that .12, or 12% of both within person and between person variance in internalizing problems and 9% of between person and 8% of within person variance in intrapersonal strengths were explained above and beyond the unconditional model (Finch, Bolin & Kelley, 2014). The parameters for the covariates can be found in Tables 1 and 2. Hypothesis 1: Higher youth participation, on average, relates to higher strengths and lower problems Next, frequency of extracurricular involvement was added to both covariate models at levels one and two.…”
Section: Resultsmentioning
confidence: 96%